The measurement of the Islamic values for muslim workers - Pasaribu, Popy Novita; Indupurnahayu, Indupurnahayu (Jurnal Manajemen, 2018)
The objectives of this study were to set up an instruments to measure Islamic values and meaning of prayers (sholat.) The Islamic values consisted of tauhid (unity), khilafah (trusteeship) and adalah (justice). Factors of pray essence consist of 6 (six) variables namely concentration, understanding, respect, fear and admiration, hope for mercy and bless and shamefornegligence. This study took place in Islamic Banks namely Bank Muamalat Indonesia (BMI) and BNI Syariah. Data analysis used for this study was Confirmatory Factor Analysis (CFA). The results showed all indicators that reflected the Islamic values were valid and reliable that was consisted 22 item questions.Construct reliability (CR) and variance extracted (VE) for Islamic values were 0,79 and 0,58. Concentration, understanding, respect, fear and admiration,indicatedthe meaning of prayer that were valid and reliable (CR 0,90 and VE 0,69), consisted nine item questions. Spiritualityin the workplacecan bedevelopedthrough theapplication ofIslamic valuesand prayer and it could be measured by these instruments.